Avulsion of the flexor digitorum tendon secondary to enchondroma of the distal phalanx - Wong, Winnie (Pulsus Group Inc, 2004)
Flexor digitorum profundus (FDP) tendon avulsion is a common injury in sports. This is secondary to forced extension against flexor digitorum profundus contraction. However, avulsion injury of the FDP tendon secondary to an enchondroma of the distal phalanx is extremely rare. There have only been three previous reports of such an occurrence. This report describes a fourth case of an avulsion injury of the FDP tendon secondary to enchondroma of the distal phalanx of the fourth digit.